A nonerythropoietic derivative of erythropoietin protects the myocardium from ischemia–reperfusion injury - Fiordaliso, Fabio (National Academy of Sciences, 2005)
The cytokine erythropoietin (EPO) protects the heart from ischemic injury, in part by preventing apoptosis. However, EPO administration can also raise the hemoglobin concentration, which, by increasing oxygen delivery, confounds assignment of cause and effect. The availability of EPO analogs that do not bind to the dimeric EPO receptor and lack erythropoietic activity, e.g., carbamylated EPO (CEPO), provides an opportunity to determine whether EPO possesses direct cardioprotective activity. In vivo, cardiomyocyte loss after experimental myocardial infarction (MI) of rats (40 min of occlusion with reperfusion) was reduced from ≈57% in MI-control to ≈45% in animals that were administered CEPO daily for 1 week (50 μg/kg of body weight s.c.) with the first dose administered intravenously 5 min before reperfusion. CEPO did not increase the hematocrit, yet it prevented increases in left ventricular (LV) end-diastolic pressure, reduced LV wall stress in systole and diastole, and improved LV response to dobutamine infusion compared with vehicle-treated animals. In agreement with the cardioprotective effect observed in vivo, staurosporine-induced apoptosis of adult rat or mouse cardiomyocytes in vitro was also significantly attenuated (≈35%) by CEPO, which is comparable with the effect of EPO. These data indicate that prevention of cardiomyocyte apoptosis, in the absence of an increase in hemoglobin concentration, explains EPO's cardioprotection. Nonerythropoietic derivatives such as CEPO, devoid of the undesirable effects of EPO, e.g., thrombogenesis, could represent safer and more effective alternatives for treatment of cardiovascular diseases, such as MI and heart failure. Furthermore, these findings expand the activity spectrum of CEPO to tissues outside the nervous system.